Impact of dimethyl sulfoxide on irradiation-related DNA double-strand-break induction, -repair and cell survival - Zwicker, Felix; Hauswald, Henrik; Debus, Jürgen; Huber, Peter E.; Weber, Klaus-Josef (Radiation and environmental biophysics, 2019)
Dimethyl sulfoxide (DMSO) is an effective radical scavenger and, when added to cells, reduces the initial number of radiation-induced DNA double-strand breaks (DSB). The aim of this study was to investigate modification by DMSO of both DSB induction and DSB repair by means of pulsed-field gel electrophoresis (PFGE) as well as gamma-H2AX immunofluorescence staining. WiDr cells (human colon carcinoma provided by DKFZ) were incubated with 2% DMSO for 2 h (or mock-treated) prior to irradiation with varying X-ray doses and subsequent incubation for repair. Sample processing for PFGE analysis or counting of γ-H2AX foci was performed according to standard protocols. Effects on apoptosis induction and cell survival were investigated additionally by standard protocols. DMSO reduced DSB yield after 20-80 Gy measured by PFGE. A qualitatively similar result was found after low-dose irradiation (1 Gy) using γ-H2AX immunofluorescence staining. During incubation for repair, both DNA fragment rejoining (PFGE) as well as γ-H2AX foci removal occurred at a reduced rate when cells had been pre-treated with DMSO. But this effect was clearly more pronounced for the PFGE-analyzed double-strand breakage, particularly at early repair times. WiDr cells treated with DMSO (2%) showed a significantly increased clonogenic survival after irradiation doses above 8 Gy. Apoptosis rates were not changed by DMSO. The radio-protective effect of DMSO, well known from other PFGE studies, could be confirmed for the formation of γ-H2AX foci. DSB generated in the presence of DMSO were less rapidly repaired. DMSO showed radio-protective effects on clonogenic survival but not on apoptosis.
Gesehen am 01.08.2019